Schooner and whaleboat, Repulse Bay, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
Port view of a whaling schooner at anchor in Repulse Bay, Hudson Bay, Canadian Arctic, September 25, 1901. Two men and a whaleboat can be seen in the foreground. Scene is described as ""showing schooner at anchor, Repulse Bay, looking east, boiling out oil."" Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo 72, #166.Number 166 is etched into emulsion on lower part of plate. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Comer's journal dates this event one day earlier.